X-Ray Lithography for Nanofabrication: Is There a Future? - Bharti, Amardeep; Turchet, Alessio; Marmiroli, Benedetta (Frontiers in Nanotechnology, 2022)
X-ray lithography has been first proposed almost 50 years ago, and the related LIGA process around 25 years ago. It is therefore a good time to make an analysis of the technique, with its pros and cons. In this perspective article we describe XRL latest advancements. First, we report the improvement in the fabrication of high aspect-ratio and high-resolution micro/nanostructures. Then, we present the radiation assisted synthesis and processing of novel materials for the next generation of functional devices. We finally draw our conclusion on the future prospects of the technique.